Global analysis of protein lysine lactylation profiles in the marine bacterium Photobacterium damselae subsp. damselae - Yu, Yongxiang; Liu, Haozhe; Wang, Chunyuan; Wang, Yingeng; Rong, Xiaojun; Liao, Meijie; Li, Bin; Yi, Xingling; Zhang, Zheng (Frontiers in Microbiology, 2025)
Lysine lactylation (Klac) is a recently discovered post-translational modification (PTM) widespread across species, playing a crucial role in cellular processes and associated with pathological conditions. Photobacterium damselae subsp. damselae, a marine bacterium within the Vibrionaceae family, is a notable pathogen in aquaculture, offering a valuable model for investigating the evolution of pathogenicity from environmental ancestors and assessing the impact of genetic diversity-generating mechanisms on bacterial populations. Therefore, we conducted the first systematic analysis of Klac modification in P. damselae using highly sensitive proteomic techniques. A total of 1,352 Klac modification sites were identified on 486 proteins. The analysis of GO annotations and KEGG pathways for the identified Klac-modified proteins revealed their widespread distribution in subcellular compartments, indicating their involvement in diverse cellular functions and metabolic pathways, particularly in ribosome and protein biosynthesis, as well as central carbon metabolism. Furthermore, 20 highly connected Klac protein clusters were extracted from the global protein-protein interaction (PPI) network, indicating that Klac modification tends to occur on proteins associated with specific functional clusters. These findings enhance our understanding of the functional role of Klac modification and provide a dataset for further exploration of its impact on the physiology and biology of P. damselae.